Efektifitas pupuk organic cair limbah sajen (limbah sayuran dan tajin) terhadap pertumbuhan tanaman cabai (capsicum annum l) - Arista, Nor Isnaeni Dwi; Azizah, Nurul (Journal of Waste and Sustainable Consumption, 2024)
Background: Consumption green vegetables domestic is so high because of an awareness to start healthy live, it will generate green vegetable waste of a leaf that is not cooked because it is eaten caterpillar or vegetable stale that are not suitable consumption at home. Besides green vegetable waste, in the house also produced waste water from washing rice ( tajin ), basically Indonesian always eats rice, hence waste water from washing rice ( tajin ) will be produced every day. Conclusion: Waste water from washing rice ( tajin ) cause many spent, while green vegetable waste will cause pollution smell to the environment. Solution the both of waste has liquid organik fertilizer is making green vegetable waste and waste water from washing rice that can increase the growth of plants. Methods: A method of writing that is used is carried out the identification of a problem, study of literature, an analysis of the potential, design and strategy. Findings: The treatment aims to understand the organik fertilizers green vegetable waste and waste water from washing rice can increase the higher of plants and the leaves of red chili.